Leadership Behaviour and Its Relation With Active Communication Skills Of Soccer Coaches - Abdul ghani, Safwan; Yousif, Ali (Journal of Physical Education, 2019)
The research aim at identifying  the relationship between leadership behavior and effective communication skills of football coaches from the players’ point of view. A descriptive method was used on (526) players and (20) coaches from the Iraqi Premier League season (2019-2018). The subject of the researcher were (60) players from four clubs. The scales of   leadership behavior and effective communication skills by Mustafa Abu Zeid and Mohammed Hassan Allawi were used in this study,  and the answers were obtained by conducted the scales on  players. According to the results, the researchers concluded that there is a significant correlation between the leadership behavior and the effective communication skills of football coaches.